Determinant Factors of Retail Trading Company Funding Decision to Reduce Company Financial Distress - Dhiena Aprelenia Maharani (Perkumpulan Praktisi Akuntansi Indonesia, 2022)
Retail trading companies are one of the pioneers in supporting Indonesia's GDP growth with a contribution of 12.56%, and still making a high and positive contribution in the first quarter of 2020. A high contribution does not guarantee that the company's financial condition is adequate. BPS data (2020) shows that there was a decline in revenue for trading companies during the pandemic. Companies must establish appropriate funding policies to improve efficient business operations so as not to experience financial distress that could potentially bankrupt. This study aims to analyze the determinants in determining funding that can reduce the financial distress of retail trading companies. The data used are the financial statements of retail companies from 2018 and 2019 with the method used is descriptive quantitative. Path analysis method to analyze hypotheses using the SME model in SPSS AMOS 26. The results of this study indicate; (i) company size 0.335, (ii) tax 0.196, and (iii) revenue growth 0.195 are determinants of funding, but they cannot reduce financial distress. If the manager decides to finance using these three factors, it will not affect the company's financial distress